The Great American novel - Williams, William Carlos (Washington, D.C. : National Public Radio, 1980)
In this panel discussion, novelists Francine du Plessix Gray and Larry McMurtry join with William McPherson of the Washington post to consider the present and future state of the novel in America. Topics include: what makes a novel great, the death of the novel, how authors are inspired to begin a novel, and other topics. Includes a question-and-answer session.
Broadcast Oct. 1, 1981, on National Public Radio.
Recorded at a National town meeting held at the Kennedy Center in Washington, D.C.
Keywords: American fiction -- 20th century -- History and criticism